The Effect of Combination of Quercetin And Glibenclamide on Myocardial Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) Expression In Type 2 Diabetic Rat - Hendrawati, Asri; Akhmad, Syaefudin Ali; Sadewa, AH; Tasmini, - (Bangladesh Journal of Medical Science, 2017)
Background. Diabetes mellitus (DM) is a metabolic disorder syndrome that marked by hyperglycemia. The main macrovascular complication is heart failure due to diabetic cardiomyopathy. Hyperglycemia can increase reactive oxygen species (ROS) and lipid peroxidation that induce cellular damage. Quercetin is an antioxidant that reduce hyperglycemia and ROS by modify the expression of nuclear factor erythroid 2-related factor 2 (Nrf 2). Objective. The aim of this research was to investigate the effect of combination of quercetin and glibenclamide on myocardial nuclear factor erythroid 2-related factor 2 (nrf 2) expression in type 2 diabetic rat compared with no combination. Methods. The rats were divided randomly into nine groups (each group consisted of four rats). The control group consist of a normal group that received placebo, DM control groups that received placebo and glibenclamide and intervention groups received quercetin 5, 20 and 80 mg/kgbw/day and combination of quercetin with 5 mg/kgbw/day of glibenclamide orally for a period of four weeks. The expression of myocardial Nrf 2 was measured by immunohistochemistry. Data was analyzed by ANOVA and p<0.05 was considered as significant. Results. Twenty and 80 mg/kgbw/day of quercetin with or without combination with glibenclamide orally for a period of four weeks increase myocardial Nrf2 expression higher than placebo (p<0.05). Eighty mg/kgbw/day of quercetin increase myocardial Nrf2 expression higher than 5 and 20 mg/kgbw/day (p<0.05). Conclusion. From this study it can be suggested that there are significant different in expression level of myocardial Nrf2 of type 2 DM after a combination of quercetin and glibenclamide, quercetin alone, glibenclamide alone and placebo. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.302-306